ANALISIS POTENSI LIKUIFAKSI BERDASARKAN UJI PENETRASI STANDAR (SPT) (STUDI KASUS: PEMBANGUNAN FLY OVER JL. TUANKU TAMBUSAI – JL. SOEKARNO HATTA PERKANBARU) - Gustika, Rani Ardeylina; Yusa, Muhamad; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia is the country that located and surrounded by three great continental plates, where the earthquakes are usually happens. This kind of phenomenon has some direct impacts, which one of them is soil liquefaction. Soil liquefaction is a phase transition process from solid to liquid phase due to increasing the pore water pressure that caused by cyclic loading. This study aims to identify the susceptibility of materials to liquefaction phenomenon using the grain size distribution curve, to analyze the safety factor (FS) and liquefaction potential index (LPI). In order to do this study, one bore holes were observed by using standard penetration test (SPT) to evaluate the liquefaction potential phenomenon. The values taken for the peak ground acceleration (PGA) are 0,250 g, 0,288 g and 0,315 g while the values of 5,00, 6,45 and 7,90 were taken as moment magnitude (Mw). The results of this study shows that the materials are susceptible to liquefied based on grain size distributions. Furthermore, the location has a potential of liquefaction, and give values between 0,250-11,084 with a low to very high of LPI category.Keywords: soil liquefaction, susceptibility, safety factor, liquefaction potential index.